Anticipated Shocks and Exchange Rate Dynamics - Wilson, Charles A. (Journal of Political Economy, 1979)
The paper extends Dornbusch's analysis of exchange rate dynamics to include the case where changes in government policy are anticipated before they occur. It is demonstrated that simply the announcement of an expansionary policy will cause the exchange rate to jump, which induces an expansionary impact on the economy even before the policy is implemented.